Online Single Submission in the Perspective of Economic Analysis Of Law - Fajar Sugiarto; Erny Herlin Setyorini (Universitas Muhammadiyah Sidoarjo, 2018)
The demands of the development of globalization have spurred developing countries, including Indonesia, to adjust themselves as soon as possible, one of them is by implementing legal development and developing policy strategies to be able to balance and meet existing demands. Reform reform is a strategic and systematic step to improve the quality of regulations in order to encourage the business and investment climate in Indonesia. Apart from having to be taken, this step must also be adjusted to the world viewpoint of measuring the quality of regulation in Indonesia, which is adjusted to Ease of Doing Business (user friendly), measured by time, procedures, and costs incurred by investors who want do business and invest in Indonesia. Other acceleration efforts The Indonesian government has just taken a policy related to Online Single Submission (OSS). This OSS implementation has prospects and all the challenges. This paper examines analyzing the efficiency and effectiveness of OSS implementation through economic analysis of law (EAL).